Distinct cellular expression of beta I- and beta II-subspecies of protein kinase C in rat cerebellum - Ase, K (J Neurosci, 1988)
Immunohistochemical and biochemical studies with subspecies-specific antibodies have revealed that beta I- and beta II-subspecies of protein kinase C, which result from alternative splicing of a single RNA transcript, show different regional expression in rat CNS. In the cerebellar cortex, beta I-subspecies is localized mainly in the granular layer, whereas beta II-subspecies is found predominantly in the molecular layer, most apparently in the presynaptic nerve endings that terminate at Purkinje cells. These distribution patterns are in sharp contrast to that of gamma-subspecies, which is most abundant within the Purkinje cells. The different patterns of expression imply that the multiple subspecies of protein kinase C may each have a specific function in modulating the neuronal activity of particular cell types.